Hollow fiber separation membrane, its preparation method, and its application
Patent Information
- Application Number
- JP2024549462
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-07-20
- Filing Date
- 2022-11-29
- Publication Date
- 2025-03-07
AI Technical Summary
【0020】 本発明は、上記技術的解決策を通じて、次の有益な効果を提供することができる: (1)ポリベンゾイミダゾール材料の相転移は、塗布された層の中の溶媒の揮発によって達成されて、分離特性を有する外側選択層を生成する; (2)ガス分離膜の機械的特性は、内部支持体補強によって向上し、膜繊維の機械的特性に対する高温、高圧、および高流率ガス分離システムなどの要求を満たすことができ、ガス分離膜の応用を拡大する; (3)キャスティング溶液の支持体の中への浸透が達成され、ボア流体によって誘起される非溶媒誘起相分離によって多孔性構造を有する遷移層が得られ、その結果、選択層が脱落することが防止される; (4)外側選択層の厚さを、紡糸工程の間に本発明の手段によって制御することができる。
Smart Images

Figure 2025506269000001_ABST
Abstract
Description
Detailed Description of the Invention
[0001] [Technical field] The present invention relates to the field of membrane technology, in particular to a novel hollow fiber membrane, its preparation method and its use.
[0002] 〔background〕 Helium and hydrogen are gases with smaller molecules and are both very important industrial gases.
[0003] Helium is mainly prepared by purifying the gases accompanying the mining of natural gas and shale gas. The process of extracting helium from natural gas and shale gas can be divided into low-temperature processes and non-low-temperature processes. Low-temperature processes are currently commonly used methods in industrialization. Industrial processes involving temperatures below -100°C are generally classified as low-temperature processes, and the extraction of helium from natural gas and the liquefaction of helium are typical low-temperature processes with the lowest low-temperature separation temperature among the low-temperature processes of natural gas. The low-temperature helium extraction process has high energy consumption and complex equipment. Membrane separation helium purification technology avoids various phase change processes and violent chemical reactions, has low energy consumption, small equipment, and high safety.
[0004] Hydrogen is both a clean energy carrier and a secondary energy source. The products during the production of hydrogen from fossil fuels include N2, CO, CH4, CO2, etc., which need to be separated and refined. With the increasing global demand for clean and efficient energy sources, the production and refinement of hydrogen are also gaining more and more attention.
[0005] In order to meet the demand for helium and hydrogen, it is urgent to develop an efficient, environmentally friendly, safe and reliable method for purifying helium and hydrogen. The demand for membrane separation technology for key membrane materials, especially high-end membrane materials, is particularly urgent.
[0006] CN113318609A discloses a method for producing a rigid network microporous hydrogen membrane with high permeability and selectivity. However, the membrane in this application has limited selectivity to hydrogen and cannot produce high purity hydrogen or helium products.
[0007] CN112142980B discloses a hyperbranched polybenzimidazole-polysiloxane block copolymer, its preparation method, and its use. The block copolymer forms a soft-hard, hydrophilic-hydrophobic phase-separated structure by combining the soft segment of PDMS with the hard segment of HBPBI, and the hydrophobic segment of PDMS with the hydrophilic segment of HBPBI, so that a proton transfer channel is constructed through the phase-separated structure of the two segments. In addition, the hyperbranched structure of HBPBI can accommodate more phosphoric acid, and finally high proton conductivity is obtained. However, this material has insufficient strength and breaking elongation, and cannot be used to prepare a gas separation membrane that can withstand high pressure.
[0008] US20160375410A1 discloses a method for preparing a PBI asymmetric hollow fiber membrane and its use, and the PBI asymmetric hollow fiber membrane prepared by the non-solvent induced phase separation technology in this application has a permeability of 108 GPU, a selectivity of H2 / CO2 of 23.7, and a selectivity of H2 / N2 of 129 at 250°C. However, the membrane is prone to defects during the phase inversion process, which greatly affects the selectivity and fails to achieve the true separation effect of PBI.
[0009] Therefore, the development of a membrane material that has a dense selective layer, is easy to prepare, and can exert a high separation effect for PBI is of great significance.
[0010] Summary of the Invention The present invention aims to provide a novel hollow fiber membrane, a preparation method thereof, and its use, in order to overcome the problems that the surface of the hollow fiber membrane prepared by non-solvent induced phase separation is prone to defects, or the material strength and breaking elongation are insufficient, and therefore cannot be used to prepare a gas separation membrane that can withstand high pressure in the prior art. The hollow fiber membrane of the present application has high selectivity and good mechanical properties.
[0011] In order to achieve the above object, one aspect of the present application is to A support; A selection layer; a transition layer between the support and the selective layer, the transition layer being at least partially embedded within the support.
[0012] According to some embodiments, in the hollow fiber membrane of the present application, the transition layer and the selective layer comprise the same polymer; Preferably, the transition layer and the selective layer comprise the same polymer, and the transition layer and the selective layer are formed from the same casting solution; More preferably, the transition layer and the selective layer comprise the same polymer, the transition layer and the selective layer are formed from the same casting solution, and the transition layer and the selective layer are formed by non-solvent induced phase separation and thermally induced phase separation, respectively. According to some embodiments, the transition layer has a porous structure (porous). According to some embodiments, the transition layer is porous and the selective layer is a dense layer.
[0013] Another aspect of the present invention is a method for producing a A support; a selective layer attached to an outer surface of the support; a transition layer embedded within the support; the support is a microporous hollow fiber membrane, The transition layer has a porous structure; the selective layer is made of polybenzimidazole; The number average molecular weight of the polybenzimidazole is 5×104 ~30×10 4 The present invention provides a hollow fiber membrane,
[0014] One aspect of the present application is a method for preparing a hollow fiber membrane, comprising the steps of: (1) preparing a casting solution containing a polymer; (2) applying the casting solution onto a support, where a portion of the casting solution penetrates into the support, thereby obtaining a primary film applied onto the support; (3) heating the primary film to form a selective layer; and (4) injecting a bore fluid into an inner tube of the support to induce non-solvent induced phase separation of the casting solution that has permeated into the support to produce a transition layer; The present invention provides a method for producing a pharmaceutical composition comprising the steps of:
[0015] Optionally, the method for preparing the hollow fiber membrane of the present invention further comprises, after formation of said transition layer, the step of heating to remove substantially all of said solvent.
[0016] A further aspect of the present invention is (1) Mixing polybenzimidazole, an acid (solvent), an optional volatile solvent, and optional additives to obtain a casting solution, wherein the polybenzimidazole has a number average molecular weight of 5×10 4 ~30×10 4 A process in which (2) extruding the casting solution, feeding the extruded casting solution into a spinneret, and applying the casting solution onto the support by a doctor blade while pulling the support from bottom to top through the interior of the spinneret, resulting in a primary film attached to the support, where a portion of the casting solution penetrates into the support; (3) heating the primary film to form a polybenzimidazole selective layer having a dense structure; and injecting a non-solvent as a bore fluid into the inner tube of the support through a core tube to induce non-solvent-induced phase separation of a portion of the casting solution that has penetrated into the support to generate a transition layer having a porous structure; and then completely drying the hollow fiber membrane to obtain the hollow fiber membrane; The present invention provides a method for preparing a hollow fiber membrane comprising:
[0017] One aspect of the present invention provides a hollow fiber membrane prepared by the aforementioned method.
[0018] Another aspect of the present invention provides the use of the hollow fiber membrane of the present invention for the separation and purification of helium / nitrogen, helium / methane, hydrogen / nitrogen, or hydrogen / methane.
[0019] Yet a further aspect of the present invention is a method for purifying helium from a helium-containing gas, comprising the steps of: The method provides a method comprising the step of performing membrane separation using a hollow fiber membrane of the present application or a hollow fiber membrane prepared by a method of the present application.
[0020] Through the above technical solutions, the present invention can provide the following beneficial effects: (1) A phase transition of the polybenzimidazole material is achieved by volatilization of the solvent in the applied layer to produce an outer selective layer with separation properties; (2) The mechanical properties of the gas separation membrane are improved by the internal support reinforcement, which can meet the requirements of high temperature, high pressure, and high flow rate gas separation systems for the mechanical properties of membrane fibers, and expand the application of gas separation membranes; (3) The penetration of the casting solution into the support is achieved, and a transition layer with a porous structure is obtained by the non-solvent-induced phase separation induced by the bore fluid, thereby preventing the selective layer from falling off; (4) The thickness of the outer selective layer can be controlled by means of the present invention during the spinning process.
[0021] When polybenzimidazole is used as the polymer for preparing the casting solution, the polybenzimidazole is dissolved by an acid and optionally a volatile solvent. The resulting hollow fiber membrane incorporates an acid as a solvent, so that the polymer is protonated during the process of dissolving the polymer, which controls the packing of molecular chains during the membrane formation process and inhibits the formation of intermolecular hydrogen bonds, thereby preparing a separation membrane with both high selectivity and high permeability.
[0022] BRIEF DESCRIPTION OF THE DRAWINGS FIG. 1 is a schematic diagram of the spinneret configuration used to produce the primary film and transition layer of the present invention.
[0023] FIG. 2 is a schematic diagram of a process of the present invention for producing a primary film and a transition layer using the spinneret of FIG.
[0024] FIG. 3 is a schematic cross-sectional SEM image of the hollow fiber membrane prepared in Example 1 of the present invention.
[0025] FIG. 4 is a cross-sectional SEM image of the selective layer of the hollow fiber membrane prepared in Example 1 of the present invention.
[0026] FIG. 5 is a cross-sectional SEM image of the inner surface of the hollow fiber membrane prepared in Example 1 of the present invention.
[0027] FIG. 6 is an SEM image of the outer surface of the hollow fiber membrane prepared in Example 1 of the present invention.
[0028] FIG. 7 is an SEM image of the inner surface of the hollow fiber membrane prepared in Example 1 of the present invention.
[0029] FIG. 8 is an SEM image of the hollow fiber membrane prepared in Example 4 of the present invention.
[0030] FIG. 9 is an SEM image of the hollow fiber membrane prepared in Example 5 of the present invention.
[0031] FIG. 10 is an SEM image of the hollow fiber membrane prepared in Comparative Example 1.
[0032] FIG. 11 is a schematic diagram of a method of the present invention for purifying helium from a helium-rich gas.
[0033] Detailed Description The range endpoints and any values disclosed herein are not intended to be limited to the exact ranges or values, and these ranges or values should be understood to include values close to said ranges or values. For numerical ranges, the various range endpoints, the various range endpoints and individual point values, the individual point values may be combined with each other to obtain one or more new numerical ranges, and these new numerical ranges should be considered as specifically disclosed herein.
[0034] References herein to "one embodiment" or "some embodiments" mean that a feature, structure, or characteristic described in connection with the embodiment or embodiments is included in at least one embodiment. These features, structures, or characteristics may be combined in any suitable manner in one or more embodiments.
[0035] As explained above, the present invention provides A support; A selection layer; a transition layer between the support and the selective layer, the transition layer being at least partially embedded within the support.
[0036] In the present invention, the support is tubular, the wall of the support has pores and / or openings, and at least a portion of the transition layer is embedded in the pores and / or openings in the wall of the support.
[0037] In the present invention, the transition layer and the selective layer comprise the same polymer. In some embodiments, the transition layer and the selective layer are formed by the same polymer.
[0038] In some embodiments, the polymer included in or forming the transition and selective layers is a polybenzimidazole.
[0039] Preferably, in some embodiments, the transition layer and the selective layer comprise the same polymer, and the transition layer and the selective layer are formed from the same casting solution. More preferably, in some embodiments, the transition layer and the selective layer comprise the same polymer, and the transition layer and the selective layer are formed from the same casting solution, and the transition layer and the selective layer are formed by non-solvent induced phase separation and thermally induced phase separation, respectively.
[0040] Non-solvent induced phase separation and thermally induced phase separation are well known in the art.
[0041] In the present invention, the selective layer is a dense layer having selectivity, and the transition layer is a layer for bonding the selective layer to the support.
[0042] In some embodiments, the present invention provides A support; a selective layer attached to an outer surface of the support; a transition layer embedded within the support; the support is a microporous hollow fiber membrane, The transition layer has a porous structure; the selective layer is made of polybenzimidazole; The number average molecular weight of the polybenzimidazole is 5×10 4 ~30×10 4 The present invention provides a hollow fiber membrane,
[0043] Polybenzimidazole (PBI) is a heterocyclic polymer with imidazole rings in the main chain, and this kind of polymer has good chemical stability, thermal stability, hydrolytic stability, and mechanical stability. As a polymer material, PBI has good processability, PBI membrane is easy to package, and the preparation cost is reasonable. PBI is particularly suitable for preparing separation membranes required for hydrogen or helium purification.
[0044] In the present invention, the volatilization of the solvent is promoted by adopting high temperature normal pressure drying or vacuum drying, so that the polymer selective layer such as the polybenzimidazole selective layer has good compactness, avoids the formation of defects, and obtains better separation performance. In addition, in the present invention, an internal support reinforcement is adopted to improve the mechanical properties of the gas separation membrane, so that the mechanical properties of the membrane can meet the requirements of high temperature, high pressure, and high flow rate gas separation systems, etc., and expand the application of the gas separation membrane. In the present invention, a transition layer with a porous structure is obtained by the non-solvent induced phase separation induced by the bore fluid, so that the selective layer is prevented from falling off.
[0045] When the selective layer comprises polybenzimidazole, the present invention uses an organic acid, and optionally a volatile solvent, to prepare a casting solution, and the surface selective layer of the resulting hollow fiber composite membrane comprises or consists of protonated polybenzimidazole, thereby achieving higher selectivity.
[0046] In the present invention, the transition layer is obtained by non-solvent induced phase separation of a casting solution. In a preferred embodiment, the transition layer is obtained by non-solvent induced phase separation of a polybenzimidazole-containing acid solution.
[0047] In the present invention, the selective layer and the transition layer may be formed from the same casting solution. In some embodiments, the selective layer and the transition layer are formed from the same primary film, with the transition layer being formed by non-solvent induced phase separation and the selective layer being formed by thermally induced phase separation.
[0048] In the present invention, the transition layer has a porous structure. In the present invention, the selective layer is a dense layer.
[0049] According to the invention, preferably, the polymer contained in or forming the transition layer and the selective layer is polybenzimidazole. 4 ~30×10 4 Preferably, the polybenzimidazole has a number average molecular weight of 5.6×10 4 ~20×10 4 , or 8 × 10 4 ~28.7×10 4 The copolymer may have a number average molecular weight of
[0050] According to the present invention, the polybenzimidazole preferably contains one or more structural units represented by formulae (A1) to (A8).
[0051] [ka]
[0052] According to the present invention, the polybenzimidazole preferably contains one or more structural units represented by formulae (A5) to (A8).
[0053] According to the present invention, the support may be a fiber braided tube or a hollow fiber membrane, preferably a microporous hollow fiber membrane. The microporous hollow fiber membrane may be a microporous hollow fiber membrane prepared by a method such as thermally induced phase separation, melt drawing, etc. from a polymer material that cannot be dissolved by the acid used to prepare the casting solution. The support may be one or more selected from the group consisting of a fiber braided tube, a microporous polypropylene hollow fiber membrane, a microporous polyethylene hollow fiber membrane, and a microporous inorganic hollow fiber membrane. Preferably, the microporous hollow fiber membrane is a microporous polypropylene hollow fiber membrane or a microporous polyethylene hollow fiber membrane prepared by a thermally induced phase separation method.
[0054] According to the present invention, the average thickness of the hollow fiber membrane of the present invention may be 50 to 2000 μm or 100 to 2000 μm, preferably 150 to 1000 μm, more preferably 180 to 500 μm.
[0055] According to the present invention, when the support is a microporous hollow fiber membrane, the porosity of the support may be 30 to 90%, preferably 50 to 80%. In some embodiments, the pore size of the support may be, for example, 10 nm to 20 μm. The porosity is measured by a nitrogen adsorption method.
[0056] According to the invention, the average thickness of the tube wall of the support may be 50 to 2000 μm or 100 to 2000 μm, preferably 300 to 1800 μm, more preferably 500 to 1500 μm.
[0057] According to the present invention, the average thickness of the selective layer may be from 100 to 50000 nm. Preferably, in some embodiments, the thickness of the selective layer may be from 200 to 5000 nm.
[0058] According to the present invention, the transition layer may have an average thickness of 20 to 2000 μm, preferably 50 to 1500 μm, more preferably 20 to 1000 μm.
[0059] In the present invention, at least a portion of the transition layer is embedded within at least a portion of the support. In some embodiments, the diameter of the transition layer may be the same as the diameter of the support. In some embodiments, the transition layer may extend beyond the outer surface of the support. In some embodiments, the transition layer may extend beyond the inner surface of the support.
[0060] In accordance with the present invention, the transition layer is formed from a casting solution by non-solvent induced phase separation. In some embodiments, the transition layer is formed from a polybenzimidazole-containing acid solution by non-solvent induced phase separation.
[0061] The hollow fiber membranes of the present invention have excellent properties including, for example, breaking strength, permeability, and selectivity.
[0062] According to the present invention, the breaking strength of the membrane is 10 to 500 MPa. Preferably, the membrane has a breaking strength of 50 to 250 MPa. More preferably, the membrane has a breaking strength of 52 to 210 MPa.
[0063] According to the present invention, in some embodiments, the hollow fiber membrane of the present invention may have a pure helium permeability of 0.8 to 480 GPU, a pure hydrogen permeability of 0.8 to 580 GPU, a nitrogen permeability of 0.01 to 0.7 GPU, and / or a methane permeability of 0.01 to 0.7 GPU at 100° C. and a test pressure of 0.5 MPa. Preferably, the pure helium permeability may be 3.48 to 477.5 GPU, the pure hydrogen permeability may be 3.03 to 79.6 GPU, the nitrogen permeability may be 0.016 to 0.68 GPU, and / or the methane permeability may be 0.0135 to 0.6 GPU.
[0064] According to the present invention, in some embodiments, the hollow fiber membrane of the present invention may have, at 100° C. and a test pressure of 0.5 MPa, a hydrogen / nitrogen selectivity of 110 to 300 or 110 to 235, and / or a hydrogen / methane selectivity of 125 to 360 or 125 to 260. Preferably, the hydrogen / nitrogen selectivity may be 110 to 234.1, and / or the hydrogen / methane selectivity may be 129.1 to 256.7.
[0065] According to the present invention, in some embodiments, the hollow fiber membrane of the present invention may have a helium / nitrogen selectivity of 140 to 390 or 140 to 190, and / or a helium / methane selectivity of 170 to 500 or 170 to 175 at 100° C. and a test pressure of 0.5 MPa. Preferably, the helium / nitrogen selectivity may be 141.4 to 187.5, and / or the helium / methane selectivity may be 170 to 173.8.
[0066] According to the present invention, in some embodiments, the hollow fiber membrane of the present invention may have a hydrogen / nitrogen selectivity of 200 to 550, and / or a hydrogen / methane selectivity of 200 to 860 at 25° C. and a test pressure of 0.5 MPa.
[0067] According to the present invention, in some embodiments, the hollow fiber membrane of the present invention may have a helium / nitrogen selectivity of 240 to 900 and / or a helium / methane selectivity of 200 to 2000 at 25° C. and a test pressure of 0.5 MPa.
[0068] The present invention also provides a method for producing a hollow fiber membrane.
[0069] According to some embodiments, the method of the present invention for producing a hollow fiber membrane comprises: (1) preparing a casting solution containing a polymer; (2) applying the casting solution onto a support, where a portion of the casting solution penetrates into the support, thereby obtaining a primary film applied onto the support; (3) heating the primary film to form a selective layer; and (4) injecting a bore fluid into the support to induce non-solvent induced phase separation of the casting solution that has permeated into the support to produce a transition layer; Includes.
[0070] Casting solutions and their preparation are generally known in the art. For example, the casting solution may be prepared by dissolving a polymer in a solvent. The polymer may be the polymer described above for the hollow fiber membrane. Preferably, the polymer is polybenzimidazole. Depending on the type of polymer, etc., the person skilled in the art may select the solvent. The solvent may be a single solvent or a mixed solvent.
[0071] Optionally, the casting solution may further comprise one or more additives, which may be appropriately selected by those skilled in the art according to their needs.
[0072] In some embodiments, the amount of polymer is 4-18 wt%, the amount of solvent is 77-90 wt%, and the amount of additive is 0-5 wt%, based on the total weight of the casting solution. Preferably, in some embodiments, the amount of polymer is 8-15 wt%, the amount of solvent is 80-90 wt%, and the amount of additive is 1-2 wt%, based on the total weight of the casting solution.
[0073] After preparing the casting solution, the casting solution is applied onto a support. The support may be a support as described above. Application may be performed via various methods commonly known in the art. For example, the support may be pulled through the casting solution to apply the casting solution to the support.
[0074] According to the present invention, the casting solution penetrates into at least a portion of the support. In some embodiments, the casting solution penetrates into a portion of the tube wall of the tubular support, for example, the casting solution may penetrate 10% to 150% of the thickness of the tube wall of the support. In some embodiments, the casting solution may penetrate 10% or more, 15% or more, 20% or more, 25% or more, 30% or more, 35% or more, 40% or more, 45% or more, 50% or more, 60% or more, 70% or more, 80% or more, 90% or more, 100% or more, 110% or more, etc. of the thickness of the tube wall of the support. One skilled in the art may appropriately determine the extent of penetration of the casting solution into the tube wall of the support. The method of the present invention allows the casting solution that penetrates into the tube wall of the support to maintain or substantially maintain the penetration depth when converted into the transition layer (such that the embedment depth of the resulting transition layer into the support is the same or substantially the same as the penetration depth of the casting solution). This ensures that at least a portion of the transition layer formed by the casting solution in the final finished hollow fiber membrane is embedded in the support.
[0075] After the casting solution is coated on the support, a primary film coated on the support is obtained.
[0076] The primary film can then be heated to form the selective layer. In the present invention, heating the primary film causes thermally induced phase separation, resulting in the formation of the outermost selective layer.
[0077] Heating promotes the volatilization of the solvent in the casting solution, thereby forming a polymer selective layer. Depending on the solvent used, a person skilled in the art may select an appropriate temperature to perform the heating. Optionally, the heating may be performed under normal pressure or reduced pressure. For example, hot air may be used for heating. In some embodiments, hot air may be used to perform the volatilization of the solvent. In the present invention, the heating temperature may be, for example, 80 to 300°C.
[0078] In the method of the present invention, thermally induced phase separation proceeds only to a stage where phase separation occurs in the outermost portion of the primary film (thereby forming a selective layer), but no phase separation occurs in the inner portion of the primary film, in particular, the casting solution that has penetrated into the support remains liquid and no thermally induced phase separation occurs.
[0079] After the primary film is heated to form a selective layer, a bore fluid may be injected into the support (i.e., into the inner tube of the tubular support), which causes a non-solvent induced phase separation of the casting solution that has permeated into the support to form a transition layer. In some embodiments, for example, the bore fluid may be injected after the desired selective layer is obtained. In the present invention, the injection of the bore fluid may be carried out at room temperature and atmospheric pressure.
[0080] As long as the casting solution is capable of causing non-solvent induced phase separation, the bore fluid can be selected by one skilled in the art depending on the composition of the casting solution, the material of the support, etc.
[0081] In the method of the present invention, optionally, the hollow fiber membrane may be heated after the formation of the transition layer to remove (substantially) all of the solvent. Heating may be performed at normal pressure or under reduced pressure. Depending on the solvent used, heating may be performed at an appropriate temperature selected by the skilled artisan. For example, hot air may be used for heating. In some embodiments, the same temperature used in step (3) above may be used in this step. For example, the temperature may be 80 to 300°C.
[0082] In the method of the present invention, the dense selective layer and the porous transition layer are formed from the same casting solution in two different ways, which makes the selective layer and the transition layer integrated. The method of the present invention allows the transition layer to be held within the support (i.e., embedded within the support), thereby firmly connecting the selective layer to the support and avoiding the selective layer from falling off. Furthermore, the method of the present application allows the transition layer to be porous, which can further contribute to firmly connecting the selective layer to the support.
[0083] The selective layer in this application is dense, while the transition layer is porous. As will be appreciated by those skilled in the art, there may be a transitional region at the transition from the dense selective layer to the porous transition layer. For purposes of this application, the transition region (if present) is considered to be part of the transition layer.
[0084] The hollow fiber membranes produced by the methods of the present invention also provide advantageous membrane properties including, for example, permeability and / or selectivity.
[0085] According to some embodiments, the method of the present invention for producing a hollow fiber membrane comprises: (1) mixing polybenzimidazole, an acid, an optional volatile solvent, and optional additives to prepare a casting solution containing a polymer; (2) applying the casting solution onto a support, wherein a portion of the casting solution penetrates into at least a portion of the support, thereby obtaining a primary film applied onto the support; (3) heating the primary film to form a selective layer; and (4) injecting a bore fluid into the support to induce non-solvent induced phase separation of the casting solution that has permeated into the support to produce a transition layer; Includes.
[0086] According to some embodiments, the method of the present invention for producing a hollow fiber membrane comprises: (1) mixing polybenzimidazole, an acid, an optional volatile solvent, and optional additives to obtain a casting solution, wherein the polybenzimidazole has a number average molecular weight of 5×10 4 ~30×10 4 A process in which (2) using a spinneret to prepare the primary film and the transition layer, and using a microporous hollow fiber membrane as the support; (3) extruding the casting solution outward, feeding the extruded casting solution into the spinneret, and applying the casting solution onto the support by a doctor blade while pulling the support from bottom to top through the inside of the spinneret, thereby obtaining the primary film attached to the support, and a portion of the casting solution penetrates into the support; (4) heating the primary film to form a polybenzimidazole selective layer having a dense structure; and injecting a non-solvent as a bore fluid into the support through a core tube to promote non-solvent induced phase separation of a portion of the casting solution that has penetrated into the support to produce the transition layer having a porous structure; and then heating to remove the solvent to obtain the hollow fiber membrane; Includes.
[0087] According to the present invention, preferably, the polybenzimidazole is 5×10 4 ~30×10 4 , or 5 × 10 4 ~28.7×10 4 and more preferably, the polybenzimidazole has a number average molecular weight of 8×10 4 ~28.7×10 4 , or 5.6 × 10 4 ~20×10 4 The number average molecular weight is
[0088] According to the present invention, the polybenzimidazole contains one or more of the structural units represented by formulas (A1) to (A8).
[0089] [ka]
[0090] According to the present invention, the polybenzimidazole preferably contains one or more of the structural units represented by formulae (A5) to (A8).
[0091] According to the invention, the polybenzimidazole and the support may be the same as those described above for the hollow fiber membrane.
[0092] Optionally, in the present invention, the support may be modified before coating. There is no particular limitation on the modification method. For example, the modification may include blending the material used to prepare the support, for example using a polymer blend, subjecting the support to chemical treatment, physical vapor deposition, ultraviolet irradiation, heat treatment, mechanical treatment, etc.
[0093] The inventors of the present invention found that, preferably, polybenzimidazole is protonated in the dissolution process by using a combination of organic acid and volatile solvent to inhibit the formation of intermolecular hydrogen bonds, increase the flexibility of polymer molecular chains, and the polymer is more likely to be closely packed in the membrane formation process, and the resulting hollow fiber composite membrane has high selectivity. Meanwhile, the volatilization of the solvent is promoted by using high temperature and high pressure film coating and high temperature normal pressure / vacuum drying, so that the polybenzimidazole selective layer has good compactness, avoids the formation of defects, and obtains better separation performance. In addition, the mechanical properties of the gas separation membrane are improved by the internal support reinforcement, which can meet the requirements of high temperature, high pressure, and high flow rate gas separation systems and the like for the mechanical properties of the membrane, expanding the application of the gas separation membrane. In addition, a transition layer with a porous structure is obtained by the non-solvent induced phase separation caused by the bore fluid, which prevents the selective layer from falling off.
[0094] According to the present invention, in some embodiments, the acid is a monoacid.Preferably, the acid is one or more selected from the group consisting of hydrochloric acid, hydrofluoric acid, and methanesulfonic acid.More preferably, the acid is methanesulfonic acid.During the membrane formation process, the organic acid induces the occurrence of protonation, suppresses the formation of intermolecular hydrogen bonds between polymer molecules, reduces the rigidity of the polymer, and allows polymer molecular chains to be more closely packed together, which is believed to improve the separation performance of low molecular gases such as hydrogen, helium, etc.
[0095] According to the present invention, the bore fluid may be one or more of water, ethanol, methanol, isopropanol, acetone, and tetrahydrofuran.
[0096] According to the invention, the volatile solvent may be ethanol and / or tetrahydrofuran.
[0097] According to the present invention, the additive may be one or more selected from the group consisting of lithium nitrate, calcium chloride, sodium chloride, potassium chloride, polyethylene glycol, and polyethylene oxide. Preferably, the additive is selected from lithium nitrate and / or potassium chloride.
[0098] According to the present invention, in some embodiments, based on the total weight of the casting solution, the amount of polybenzimidazole is 4-18 wt%, the amount of the acid is 77-90 wt%, the amount of the volatile solvent is 0-10 wt%, and the amount of the additive is 0-5 wt%. Preferably, based on the total weight of the casting solution, the amount of polybenzimidazole is 8-15 wt%, the amount of the acid is 80-90 wt%, the amount of the volatile solvent is 1-5 wt%, and the amount of the additive is 1-2 wt%. It should be noted that in the present invention, the sum of the components of polybenzimidazole, acid, volatile solvent, and optional additive is 100 wt%.
[0099] In some embodiments, the casting solution can be obtained by adding polybenzimidazole into the acid, adding a volatile solvent (if used) and additives (if used), and mixing. Optionally, stirring and heating may be performed during mixing. In some embodiments, the mixing conditions may include a temperature of 25-160°C and a time of 2-72 hours, preferably, the temperature is 80-160°C and the time is 12-48 hours. The stirring is not particularly limited and may be conventionally selected by those skilled in the art. Preferably, the stirring speed of the stirring may be 20-500 rpm.
[0100] After the casting solution is prepared, the casting solution is applied onto the surface of the support. In some embodiments, the casting solution may be blade coated onto the surface of the support. According to the present invention, the casting solution may be blade coated onto the surface of the support at a certain temperature and pressure to obtain a primary film having a certain thickness. The blade coating conditions may include a temperature of 60 to 250°C, preferably 80 to 180°C. In the present invention, the blade coating pressure is not particularly limited. Preferably, the pressure may be 10 to 2000 KPa, more preferably 500 to 1200 KPa.
[0101] In the present invention, the thickness of the primary film, and therefore the thickness of the selective layer, can be controlled by controlling the distance between the doctor blade and the outer wall of the support during the blade coating process. In some embodiments, the thickness of the blade-coated film (primary film) (the distance between the doctor blade and the outer wall of the support) may be 10-300 μm. Of course, the spacing distance between the doctor blade and the outer wall of the support may be adjusted by those skilled in the art according to the desired thickness of the primary film.
[0102] In some embodiments, the casting solution is extruded into a spinneret, and the casting solution contacts the support in the spinneret. The contact time is not particularly limited. For example, the contact time may be 1 to 15 seconds, and preferably, the contact time is 1 to 10 seconds. In the present invention, the pressure is not particularly limited. For example, the pressure may be 10 to 2000 KPa. For example, the pressure may be 0 to 0.2 MPa (gauge pressure). For example, the pressure may be 0.02 to 0.1 MPa (gauge pressure).
[0103] According to the present invention, after the casting liquid is applied onto the support (e.g., blade coating), the support with the attached primary film may be pulled and sent into a heating device. The solvent in the outer layer of the primary film is evaporated by heating to form a polymer selective layer, such as a polybenzimidazole selective layer, attached to the support. For example, the heating may be performed by hot air. The heating may be performed under normal pressure or reduced pressure. For example, the heating may be performed at -0.1 MPa to 0 MPa (gauge pressure). In some embodiments, the conditions for promoting the evaporation of the solvent by heating may include a temperature of 80 to 300°C. In some embodiments, the heating may be performed by using hot air. Depending on the solvent used, the desired evaporation rate, etc., the skilled person may appropriately select the heating conditions. In the present invention, the device for heating is not particularly limited and may be, for example, an oven. In some embodiments, the heating temperature may be 100 to 280°C, and the heating time may be 2 to 24 hours. Preferably, the heating temperature is 120 to 150°C, and the heating time is 5 to 12 hours.
[0104] After the outermost polymeric selective layer is formed by heating, a bore fluid may be injected into the support, the bore fluid inducing a non-solvent induced phase separation of the casting solution that has permeated into the support to produce a transition layer, for example, a bore fluid as described above.
[0105] In the method of the present invention, optionally, the hollow fiber membrane may be heated after the formation of the transition layer to remove (substantially) all of the solvent. Heating may be performed under normal pressure or reduced pressure. Depending on the solvent used, a person skilled in the art may select an appropriate temperature for heating. For example, hot air may be used for heating. For example, the heating temperature may be 80 to 300°C.
[0106] In the present invention, optionally, the method may further comprise a step of removing residual solvent from the resulting completed membrane by a washing step (eg, water washing, ethanol washing, etc.).
[0107] Figure 1 is a schematic diagram of a spinneret configuration used to produce the primary film and transition layer of the present invention. Figure 2 is a schematic diagram of a process of the present invention for producing the primary film and transition layer using the spinneret of Figure 1.
[0108] Referring to FIG. 1 and FIG. 2, the spinneret includes a support positioner, an annular doctor blade, and a core tube. The support positioner surrounds the support and is located at one end of a casting solution cavity for containing a casting solution. A casting solution inlet and a casting solution outlet are disposed on the casting solution cavity. Preferably, the casting solution outlet is higher than the casting solution inlet. The support positioner is disposed at one end of the casting solution cavity to form a closed end, and the annular doctor blade is disposed at the other end of the casting solution cavity. The diameter of the annular doctor blade is larger than the width of the support positioner, and a gap formed by the difference in diameter between the annular doctor blade and the support positioner can be used to form a primary film. Also shown in FIG. 1 is a support holder for holding the support and pulling the support through the casting solution cavity. Also shown in FIG. 1 is the core tube. The core tube can be inserted into the inner tube of the support, and bore fluid is injected to form a flow of bore fluid inside the support. After the bore fluid is injected through the core tube, the bore fluid induces non-solvent induced phase separation to obtain a transition layer with a porous structure and avoid the drop-off of the selective layer.
[0109] With reference to FIG. 2, the process of producing the primary film and transition layer using the spinneret of FIG. 1 will be described. First, a support is selected, and the support is fixed using a support positioner. The casting solution extruded from a twin-screw extruder or a gear pump is fed into the casting solution cavity through the casting solution inlet. The support is pulled from bottom to top through the casting solution cavity and blade coated by an annular doctor blade, and a part of the casting solution penetrates into the support. A primary film attached to the support is obtained after exiting the annular doctor blade. The excess casting solution flows out through the casting solution outlet. After exiting the annular doctor blade, the support with the attached primary film is pulled and sent into a heating device, and the outer layer of the primary film is heated (e.g., heated with hot air) to promote the volatilization of the solvent, thereby forming a polymer selection layer, e.g., a polybenzimidazole selection layer, attached to the surface of the support. Then, a core tube is placed in the support, and a bore fluid is injected into the support through the core tube, and a transition layer having a porous structure is obtained from the casting solution permeated into the support by non-solvent-induced phase separation induced by the bore fluid. The transition layer is embedded in the support and is integral with the selective layer, preventing the selective layer from falling off.
[0110] The present invention also provides a hollow fiber membrane prepared by the method described above. In some embodiments, the hollow fiber membrane of the present invention is prepared by the method of the present invention for producing a hollow fiber membrane.
[0111] The hollow fiber membrane of the present invention can be used for gas separation.Therefore, the present invention also provides the use of the hollow fiber membrane of the present invention for the separation of helium / nitrogen, helium / methane, hydrogen / nitrogen, and / or hydrogen / methane.The hollow fiber membrane of the present invention can be used to separate gas by using the operation generally known in the art.
[0112] The present invention also provides a method for purifying helium from a helium-rich gas, comprising the step of performing membrane separation on the gas by using the hollow fiber membrane of the present invention.
[0113] In some embodiments, a method for purifying helium from a helium-rich gas may include subjecting the helium-rich gas to condensation via a cryogenic process, catalytic dehydrogenation, membrane separation, and pressure swing adsorption impurity removal processes, resulting in pure helium, wherein the membrane separation process includes using a hollow fiber membrane of the present invention.
[0114] In some embodiments, a method for purifying helium from a helium-rich gas may include subjecting the helium-rich gas to a condensation process through a low-temperature process, a catalytic dehydrogenation process, a membrane separation process through a helium separation membrane, and a pressure swing adsorption impurity removal process to obtain pure helium, where the condensation process conditions include a temperature of -220°C or higher, and where the membrane separation process includes using the hollow fiber membrane of the present invention.
[0115] The method for purifying helium of the present invention has the following advantages:
[0116] (1) The helium produced can be of high purity, e.g., up to 4N grade (99.99%) or even higher, which can greatly improve the efficiency of helium extraction; (2) Low temperature processes are high temperature, reducing energy consumption.
[0117] In some embodiments, the condensation conditions may include a temperature of -220°C or higher. In some embodiments, the condensation conditions may include a temperature of -210°C to -150°C and a pressure of 0.2 MPa to 10 MPa. Preferably, the condensation conditions include a temperature of -180°C to -150°C and a pressure of 3 MPa to 10 MPa.
[0118] According to the present invention, there is no specific limitation on the helium-containing gas, and there is no specific limitation on the composition of the helium-containing gas, and the method of the present invention has universal applicability. In some embodiments, the helium-containing gas may include natural gas, oil field related gas, etc. In some embodiments, the helium-containing gas may include helium, nitrogen, methane, hydrogen, and carbon dioxide. In some embodiments, based on the total volume of the helium-rich gas, the content of helium may be 5-40 volume %. Preferably, the content of helium may be 15-30 volume %.
[0119] According to the present invention, the helium-rich gas also contains optional oxygen and water, and the oxygen content is 0-8 vol. % and the water content is 0-2 vol. %, based on the total volume of the helium-rich gas.
[0120] According to the present invention, the helium-rich gas is subjected to a condensation process to achieve the effect of liquefying impurities (such as nitrogen, methane, oxygen, light hydrocarbons, etc.), and the nitrogen, methane, oxygen, and CO2 are partially removed to obtain a second mixed gas.
[0121] According to the invention, the second gas mixture is subjected to a catalytic dehydrogenation treatment to remove a portion of the hydrogen, thereby obtaining a third gas mixture.
[0122] According to the present invention, the conditions of the catalytic dehydrogenation may include a temperature of 60-120° C., preferably 60-110° C., more preferably 62-106° C. The catalytic dehydrogenation is carried out in the presence of oxygen and a catalyst, where the catalyst is a noble metal catalyst, preferably the catalyst is selected from Pt, Pb, Rh, Ru, or Au. More preferably, the catalyst is selected from Pt, Pb, or Au.
[0123] According to the present invention, the third gas mixture is subjected to the membrane separation process of the present invention to remove nitrogen, methane, oxygen, and a portion of the CO2 to obtain a fourth gas mixture.
[0124] According to the present invention, membrane separation achieves separation of helium by utilizing the difference in permeability in the process of dissolution, diffusion and desorption of each component in the feed gas under the driving of the pressure difference on both sides of the membrane. The conditions of the membrane separation process may include that the pressure on the positive pressure side of the membrane separation is greater than the pressure on the permeation side of the membrane separation. Here, the pressure on the positive pressure side of the membrane separation may be 0.2 to 10 MPa. Preferably, the pressure on the positive pressure side of the membrane separation is 0.5 to 10 MPa. More preferably, the pressure on the positive pressure side of the membrane separation is 3 to 10 MPa. The membrane separation method has the advantages of simple operation, low energy consumption, and low construction and operation costs of the apparatus.
[0125] According to the present invention, the membrane separation may be a single-stage membrane separation or a multi-stage membrane separation to purify helium. In the membrane separation, the multi-stage membrane separation means that the permeate gas is pressurized and passes through the membrane separation again as the feed gas, and the process may be 1 to 5 stages.
[0126] According to the present invention, the fourth mixed gas is subjected to an adsorptive impurity removal process to remove nitrogen, methane, oxygen, hydrogen, and part of CO2, thereby obtaining purified helium, where the helium content may be 99.986-99.996 vol.% based on the total volume of the purified helium.
[0127] According to the present invention, the conditions of the pressure swing adsorption impurity removal treatment may include an adsorption pressure of 0.2 to 15 MPa, preferably 10 to 15 MPa. In the present invention, the adsorbent used in the adsorption impurity removal treatment may be one or more selected from activated carbon, molecular sieves, metal-organic frameworks MOFs, and activated alumina.
[0128] In this application, pressures are gauge pressures unless otherwise specified.
[0129] The invention is explained in detail below by means of examples.
[0130] In the following examples and comparative examples, Polybenzimidazole was purchased from Shanghai Shengjun Plastics Technology Co., Ltd. Other reagents / agents were purchased from Beijing Yinuokai Technology Co., Ltd. Here, ethanol 99.9%, hydrochloric acid 12 mol / L, methanesulfonic acid 99.0%, and tetrahydrofuran 99.9%.
[0131] Permeability (unit GPU) test method: The gas flow rate per unit membrane area per unit time at a specific pressure difference at a specific temperature was measured. Here, 1 GPU = 10 -6 cm 3 (STP) / (cm 2 ·s·cmHg).
[0132] The selectivity α is dimensionless and is used to characterize the selective permeability of a gas component through a membrane. Selectivity is the ratio of the permeabilities of two gases through a membrane.
[0133] The breaking strength was tested using an Instron 3342 according to the ASTM D882 standard.
[0134] <Example 1> This example provided a hollow fiber membrane prepared using the method of the present invention.
[0135] (1) Polybenzimidazole A5, ethanol, and hydrochloric acid were added into methanesulfonic acid and stirred at 70°C and 0 MPa (gauge pressure) for 24 hours to achieve uniform mixing to prepare a mixed feed liquid (casting solution), where the mass contents were: 10 wt% polybenzimidazole, 3 wt% ethanol, 3 wt% hydrochloric acid, and 84 wt% methanesulfonic acid.
[0136] The structural unit of polybenzimidazole A5 is shown below:
[0137] [ka]
[0138] Here, polybenzimidazole A5 is 5.6 × 10 4 The copolymer had a number average molecular weight of 1.01 g / mol.
[0139] (2) The mixed feed liquid was heated to 240°C and extruded into a spinneret by a twin-screw extruder. Here, the spinneret shown in Figure 1 was used. The support was a polyester fiber braided tube. The casting solution contacted the braided tube in the spinneret (the height of the spinneret cavity was 10 cm) by a concentric circular composite spinning technique, the contact time was 10 seconds, and the pressure was 0.1 MPa. The support was pulled from bottom to top through the spinneret, and then the support passed through an annular doctor blade. The thickness of the polybenzimidazole primary film was controlled to be 200 μm, resulting in a polybenzimidazole primary film attached to the support. The excess casting solution flowed out through the casting solution outlet, and part of the casting solution permeated into the support.
[0140] (3) The polybenzimidazole primary film was drawn out by 100 cm in an air bath at 100 °C, then cut and kept continuously in an air bath at 100 °C for 50 min, resulting in the formation of a polybenzimidazole selective layer with a dense structure.
[0141] (4) Ethanol was introduced into the inner tube of the support through the core tube to induce phase separation and promote non-solvent-induced phase separation of a part of the casting solution that had permeated into the support to produce a transition layer with a porous structure, and then the solvent in the primary film was completely evaporated at 110°C in an oven to prepare a finished hollow fiber membrane.
[0142] The thickness of the selective layer of the produced hollow fiber membrane was about 27-29 μm. Referring to FIG. 4, FIG. 4 is a cross-sectional SEM image of the selective layer of the hollow fiber membrane prepared in Example 1 of the present invention. The transition layer was embedded in the support and had a thickness of about 380 μm (in Example 1, the transition layer extended further inward from the inner surface of the support, and therefore the support was slightly thicker), and the thickness of the embedded layer exceeded the wall thickness of the support.
[0143] The breaking strength of the hollow fiber membrane prepared in Example 1 was 160 MPa. Under a test pressure of 0.5 MPa and at 100°C, the pure helium permeability was 3.48 GPU, the pure hydrogen permeability was 3.03 GPU, the nitrogen permeability and the methane permeability were 0.016 GPU and 0.0135 GPU, respectively. The hydrogen / nitrogen selectivity and the hydrogen / methane selectivity were 189 and 224, respectively.
[0144] Figure 3 is a schematic cross-sectional SEM image of the hollow fiber membrane prepared in Example 1 of the present invention. As can be seen from Figure 3, the selective layer is located on the outer surface of the membrane, and the transition layer is embedded in the support and firmly combined with the PBI membrane.
[0145] Figure 5 is a cross-sectional SEM image of the inner surface of the hollow fiber membrane prepared in Example 1 of the present invention. As can be seen from Figure 5, the support is embedded in the transition layer, and the inner surface of the transition layer has a microporous structure.
[0146] Figure 6 is a SEM image of the outer surface of the hollow fiber membrane prepared in Example 1 of the present invention. As can be seen from Figure 6, the outer surface has a dense structure.
[0147] Figure 7 is an SEM image of the inner surface of the novel hollow fiber membrane prepared in Example 1 of the present invention. As can be seen from Figure 7, the inner surface is a transition layer with a microporous structure.
[0148] <Example 2> This example provided a hollow fiber membrane prepared using the method of the present invention.
[0149] (1) Polybenzimidazole A6, ethanol, and tetrahydrofuran were mixed with methanesulfonic acid and stirred at 80°C and 0.5 MPa pressure for 24 hours to achieve uniform mixing to prepare a mixed feed liquid (casting solution), where the mass contents were: 10 wt% polybenzimidazole, 2 wt% ethanol, 2 wt% tetrahydrofuran, and 86 wt% methanesulfonic acid.
[0150] The structural unit of polybenzimidazole A6 is shown below:
[0151] [ka]
[0152] Here, polybenzimidazole A6 is 7.2 × 10 4 The copolymer had a number average molecular weight of 1.01 g / mol.
[0153] (2) The mixed feed liquid was heated to 180°C and extruded into the spinneret by a gear pump. Here, the spinneret shown in Figure 1 was used. The support was a microporous polypropylene membrane prepared by thermally induced phase separation. The casting solution contacted the microporous polypropylene membrane in the spinneret (the height of the spinneret cavity was 10 cm) by the concentric circular composite spinning technique, the contact time was 10 seconds, and the pressure was 0.4 MPa. The support was pulled from bottom to top through the spinneret, and then the support passed through an annular doctor blade. The thickness of the polybenzimidazole primary film was controlled to be 100 μm, resulting in a polybenzimidazole primary film attached to the support. The excess casting solution flowed out through the casting solution outlet, and part of the casting solution permeated into the support.
[0154] (3) The polybenzimidazole primary film was drawn out by 200 cm in an air bath at 100 °C, then cut and kept in an air bath at 100 °C continuously for 40 min, resulting in the formation of a polybenzimidazole selective layer with a dense structure.
[0155] (4) Ethanol was introduced into the inner tube of the support through the core tube to induce phase separation and promote the non-solvent ethanol-induced phase separation of a part of the casting solution that had permeated into the support to produce a transition layer with a porous structure, and then the solvent in the primary film was completely evaporated at 100°C in an oven to prepare a finished hollow fiber membrane.
[0156] The average thickness of the produced hollow fiber membranes was about 200 μm. The thickness of the selective layer was about 2-5 μm. The transition layer was embedded in the support and had a thickness of about 200 μm.
[0157] The breaking strength of the prepared hollow fiber membrane was 155 MPa. Under a test pressure of 0.5 MPa and at 100°C, the pure helium permeability was 7.5 GPU, the pure hydrogen permeability was 6.8 GPU, the nitrogen permeability and the methane permeability were 0.04 GPU and 0.04 GPU, respectively. The helium / nitrogen selectivity and helium / methane selectivity were 187.5 and 170, respectively.
[0158] <Example 3> This example provided a hollow fiber membrane prepared using the method of the present invention.
[0159] (1) Polybenzimidazole A4 was mixed with methanesulfonic acid and stirred at 150°C and 1.0 MPa pressure for 24 hours to achieve uniform mixing to prepare a mixed feed liquid (casting solution), where the mass contents were: 18 wt% polybenzimidazole, and 82 wt% methanesulfonic acid.
[0160] The structural unit of polybenzimidazole A4 is shown below:
[0161] [ka]
[0162] Here, polybenzimidazole A4 is 6.8 × 10 4 The copolymer had a number average molecular weight of 1.01 g / mol.
[0163] (2) The mixed feed liquid was heated to 100°C and extruded into the spinneret by a gear pump. Here, the spinneret shown in Figure 1 was used. The support was a microporous polypropylene membrane (prepared by thermally induced phase separation). The casting solution contacted the support in the spinneret (the height of the spinneret cavity was 10 cm) by the concentric circular composite spinning technique, the contact time of the casting solution with the support was 2 seconds, and the pressure was 0.5 MPa. The support was pulled from bottom to top through the spinneret, and then the support passed through an annular doctor blade. The thickness of the polybenzimidazole primary film was controlled to be 100 μm, resulting in a polybenzimidazole primary film attached to the support. The excess casting solution flowed out through the casting solution outlet, and part of the casting solution permeated into the support.
[0164] (3) The polybenzimidazole primary film was drawn out by 200 cm in an air bath at 150°C, then cut and kept continuously in an air bath at 150°C for 50 min, resulting in the formation of a polybenzimidazole selective layer with a dense structure.
[0165] (4) Water was introduced into the inner tube of the support through the core tube to induce non-solvent-induced phase separation of the primary film that had not yet been phase-separated, and promote the non-solvent-induced phase separation of a portion of the casting solution that had permeated into the support to generate a transition layer with a porous structure, and then the solvent in the primary film was completely volatilized at 120°C in an oven to prepare a finished hollow fiber membrane.
[0166] The thickness of the selective layer of the produced hollow fiber membrane was about 45-50 μm. The transition layer was embedded in the support and had a thickness of about 450 μm.
[0167] The breaking strength of the prepared hollow fiber membrane was 206 MPa. Under a test pressure of 0.5 MPa and at 100°C, the pure helium permeability was 0.87 GPU, the pure hydrogen permeability was 0.81 GPU, the nitrogen permeability and the methane permeability were 0.005 GPU and 0.004 GPU, respectively. The hydrogen / nitrogen selectivity and hydrogen / methane selectivity were 162 and 202.5, respectively.
[0168] <Example 4> This example provided a hollow fiber membrane prepared using the method of the present invention.
[0169] (1) Polybenzimidazole A8 and ethanol were mixed with methanesulfonic acid and stirred at 60°C and normal pressure for 24 hours to achieve uniform mixing to prepare a mixed feed liquid (casting solution), where the mass contents were: 4 wt% polybenzimidazole, 10 wt% ethanol, and 86 wt% methanesulfonic acid.
[0170] The structural unit of polybenzimidazole A8 is shown below:
[0171] [ka]
[0172] Here, polybenzimidazole A8 is 9.7 × 10 4 The copolymer had a number average molecular weight of 1.01 g / mol.
[0173] (2) The mixed feed liquid was heated to 80°C and extruded into the spinneret by a gear pump. Here, the spinneret shown in Figure 1 was used. The support was a polypropylene fiber braided tube prepared by braiding polypropylene fibers. The casting solution contacted the support in the spinneret (the height of the spinneret cavity was 10 cm) by the concentric composite spinning technique, the contact time of the casting solution with the braided tube was 10 seconds, and the contact pressure was 0.05 MPa. The support was pulled from bottom to top through the spinneret, and then the support passed through an annular doctor blade. The thickness of the polybenzimidazole primary film was controlled to be 100 μm, and as a result, a polybenzimidazole primary film attached to the support was obtained. The excess casting solution flowed out through the casting solution outlet, and a part of the casting solution permeated into the support.
[0174] (3) The tube was cut after the length of the polybenzimidazole primary film reached 200 cm and transferred into an air bath at 150 °C for drying for 10 min, thus forming a polybenzimidazole selective layer with a dense structure.
[0175] (4) Ethanol was introduced into the inner tube of the support through the core tube to induce phase separation and promote non-solvent-induced phase separation of a part of the casting solution that had permeated into the support to produce a transition layer with a porous structure, and then the solvent in the primary film was completely evaporated at 110°C in an oven to prepare a finished hollow fiber membrane.
[0176] The thickness of the selective layer of the produced hollow fiber membranes was 400-600 nm, with a relatively clear transition region that was embedded in the support and extended through the support in some parts, and had a thickness of 200-400 μm.
[0177] The breaking strength of the prepared hollow fiber membrane was 161 MPa. Under a test pressure of 0.5 MPa and at 100°C, the pure helium permeability was 107 GPU, the pure hydrogen permeability was 95 GPU, the nitrogen permeability and the methane permeability were 0.45 GPU and 0.41 GPU, respectively. The hydrogen / nitrogen selectivity and hydrogen / methane selectivity were 211 and 231.7, respectively.
[0178] FIG. 8 shows SEM images of the hollow fiber membrane prepared in Example 4, and from left to right and top to bottom are images of the overall cross section, the selective layer and transition layer, an enlarged selective layer and transition layer, the outer surface, the inner surface (the porous transition layer), and a cross section of the support.
[0179] <Example 5> This example provided a hollow fiber membrane prepared using the method of the present invention.
[0180] (1) Polybenzimidazole A7 and ethanol were mixed with methanesulfonic acid and stirred at 60° C. and normal pressure for 72 hours to achieve uniform mixing to prepare a mixed feed liquid (casting solution), where the mass contents were: 4 wt % polybenzimidazole, 1 wt % ethanol, and 95 wt % methanesulfonic acid.
[0181] The structural unit of polybenzimidazole A7 is shown below:
[0182] [ka]
[0183] Here, polybenzimidazole A7 is 28.7 × 10 4 The copolymer had a number average molecular weight of 1.01 g / mol.
[0184] (2) The mixed feed liquid was heated to 80°C and extruded into the spinneret by a gear pump. Here, the spinneret shown in Figure 1 was used. The support was a microporous polypropylene hollow fiber membrane (average pore size 0.01 μm, porosity 65%, external contact angle 75°, its preparation method: 25 wt% polypropylene resin, 0.5 wt% maleic anhydride grafted polypropylene, 0.5 wt% polyvinylpyrrolidone, and 74 wt% soybean oil were stirred and heated at 185°C to obtain a homogeneous casting solution, after vacuum degassing and filtration, the casting solution was fed into a hollow spinneret using soybean oil as the bore fluid, and then placed in soybean oil for cooling and solidification, extracted with acetone, and air-dried to obtain a microporous polypropylene hollow fiber membrane). The casting solution was contacted with the microporous polypropylene membrane (prepared by thermally induced phase separation) in a spinneret (the height of the spinneret cavity was 10 cm) by a concentric circular composite spinning technique, the contact time of the casting solution with the support was 10 seconds, and the contact pressure was 0.1 MPa. The support was pulled from bottom to top through the spinneret, and then the support passed through an annular doctor blade. The thickness of the polybenzimidazole primary film was controlled to be 100 μm, resulting in a polybenzimidazole primary film attached to the support. The excess casting solution flowed out through the casting solution outlet, and part of the casting solution permeated into the support.
[0185] (3) The polybenzimidazole primary film was drawn out for 100 cm in an air bath at 150 °C, then cut and continuously dried in an air bath at 150 °C for 100 min, thereby forming a polybenzimidazole selective layer with a dense structure.
[0186] (4) Ethanol was introduced into the inner tube of the support through the core tube to induce phase separation and promote non-solvent-induced phase separation of a part of the casting solution that had permeated into the support to produce a transition layer with a porous structure, and then the solvent in the primary film was completely evaporated at 110°C in an oven to prepare a finished hollow fiber membrane.
[0187] The average thickness of the produced hollow fiber membranes was about 350 μm. The average thickness of the selective layer was about 1.2-2.0 μm. The transition layer was embedded in the support and had a thickness of about 30 μm.
[0188] The breaking strength of the prepared hollow fiber membrane was 63 MPa. Under a test pressure of 0.5 MPa and at 100°C, the pure helium permeability was 88.9 GPU, the pure hydrogen permeability was 76.1 GPU, the nitrogen permeability and the methane permeability were 0.66 GPU and 0.52 GPU, respectively. The hydrogen / nitrogen selectivity and hydrogen / methane selectivity were 134.7 and 170.9, respectively.
[0189] FIG. 9 shows SEM images of the hollow fiber membrane prepared in Example 5, and from left to right and top to bottom, images of the overall cross section, the selective layer and transition layer, an enlarged selective layer and transition layer, the outer surface, the inner surface, and a cross section of the support are arranged, respectively.
[0190] <Example 6> This example provided a hollow fiber membrane prepared using the method of the present invention.
[0191] (1) Polybenzimidazole A1 and tetrahydrofuran were mixed with methanesulfonic acid and stirred at 60° C. and normal pressure for 72 hours to achieve uniform mixing to prepare a mixed feed liquid (casting solution), where the mass contents were: 8 wt % polybenzimidazole, 2 wt % tetrahydrofuran, and 90 wt % methanesulfonic acid.
[0192] The structural unit of polybenzimidazole A1 is shown below:
[0193] [ka]
[0194] Here, polybenzimidazole A1 is 8.7 × 104 The copolymer had a number average molecular weight of 1.01 g / mol.
[0195] (2) The mixed feed liquid was heated to 80°C and extruded into the spinneret by a gear pump. Here, the spinneret shown in Figure 1 was used. The support was a microporous polyethylene membrane (prepared by melt spinning and drawing method, pore size 1-10μm, porosity 65-80%). The casting solution was contacted with the microporous polyethylene membrane in the spinneret (the height of the spinneret cavity was 10cm) by the concentric composite spinning technique, the contact time was 10 seconds, and the contact pressure was 0.2MPa. The support was pulled from bottom to top through the spinneret, and then the support passed through the annular doctor blade. The thickness of the polybenzimidazole primary film was controlled to be 80μm, resulting in a polybenzimidazole primary film attached to the support. The excess casting solution flowed out through the casting solution outlet, and a part of the casting solution permeated into the support.
[0196] (3) The polybenzimidazole primary film was drawn out by 100 cm in an air bath at 150°C, then cut and left in an air bath at 150°C for drying for 100 min, thus forming a polybenzimidazole selective layer with a dense structure.
[0197] (4) Tetrahydrofuran was introduced into the inner tube of the support through the core tube to induce phase separation and promote the non-solvent tetrahydrofuran-induced phase separation of a part of the casting solution that had permeated into the support to produce a transition layer with a porous structure, and then the solvent in the primary film was completely evaporated at 110°C in an oven to prepare a finished hollow fiber membrane.
[0198] The thickness of the selective layer of the produced hollow fiber membrane was about 2000 nm. The transition layer was embedded in the support and had a thickness of about 180-190 μm (average thickness about 185 μm).
[0199] The breaking strength of the prepared hollow fiber membrane was 52 MPa. Under a test pressure of 0.5 MPa and at 100°C, the pure helium permeability was 82.2 GPU, the pure hydrogen permeability was 79.6 GPU, the nitrogen permeability and the methane permeability were 0.68 GPU and 0.55 GPU, respectively. The hydrogen / nitrogen selectivity and hydrogen / methane selectivity were 120.61 and 144.7, respectively.
[0200] <Example 7> This example provided a hollow fiber membrane prepared using the method of the present invention.
[0201] (1) Polybenzimidazole A7 and tetrahydrofuran were mixed with methanesulfonic acid and stirred at 60° C. and normal pressure for 24 hours to achieve uniform mixing to prepare a mixed feed liquid (casting solution), where the mass contents were: 8 wt % polybenzimidazole, 2 wt % tetrahydrofuran, and 90 wt % methanesulfonic acid.
[0202] The structural unit of polybenzimidazole A7 is shown below:
[0203] [ka]
[0204] Here, polybenzimidazole A7 has a molecular weight of 12.6 × 10 4 The copolymer had a number average molecular weight of 1.01 g / mol.
[0205] (2) The mixed feed liquid was heated to 80°C and extruded into the spinneret by a gear pump. Here, the spinneret shown in Figure 1 was used. The support was a microporous polyethylene hydrophobic membrane with a porosity of 60-80% (prepared by melt spinning drawing method). The casting solution was contacted with the microporous polyethylene hydrophobic membrane in the spinneret (the height of the cavity of the spinneret was 10 cm) by the concentric circular composite spinning technique, and the contact time was controlled to be 10 seconds and the contact pressure was controlled to be 0.1 MPa. The support was pulled from bottom to top through the spinneret, and then the support passed through an annular doctor blade. The thickness of the polybenzimidazole primary film was controlled to be 80 μm, resulting in a polybenzimidazole primary film attached to the support. The excess casting solution flowed out through the casting solution outlet, and a part of the casting solution permeated into the support.
[0206] (3) The polybenzimidazole primary film was drawn out by 100 cm in an air bath at 150°C, then cut and left in an air bath at 150°C for drying for 100 min, thus forming a polybenzimidazole selective layer with a dense structure.
[0207] (4) Tetrahydrofuran was introduced into the inner tube of the support through the core tube to induce phase separation and promote the non-solvent tetrahydrofuran-induced phase separation of a part of the casting solution that had permeated into the support to produce a transition layer with a porous structure, and then the solvent in the primary film was completely evaporated at 110°C in an oven to prepare a finished hollow fiber membrane.
[0208] The thickness of the selective layer of the produced hollow fiber membrane was about 10-12 μm. The transition layer was embedded in the support and had a thickness of about 300 μm.
[0209] The breaking strength of the prepared hollow fiber membrane was 52 MPa. Under a test pressure of 0.5 MPa and at 100°C, the pure helium permeability was 22.6 GPU, the pure hydrogen permeability was 22.1 GPU, the nitrogen permeability and the methane permeability were 0.16 GPU and 0.13 GPU, respectively. The helium / nitrogen selectivity and helium / methane selectivity were 141.4 and 173.8, respectively.
[0210] <Comparative Example 1> (1) Polybenzimidazole A1 was mixed with methanesulfonic acid and stirred at 150°C and 1.0 MPa pressure for 24 hours to achieve uniform mixing to prepare a mixed feed liquid (casting solution), where the mass contents were: 10 wt% polybenzimidazole, and 90 wt% methanesulfonic acid.
[0211] The structural units contained by polybenzimidazole A1 are shown below:
[0212] [ka]
[0213] Here, polybenzimidazole A1 is 6.8 × 10 4 The copolymer had a number average molecular weight of 1.01 g / mol.
[0214] (2) The mixed feed liquid was heated to 140°C and extruded into the spinneret by a gear pump. Here, the spinneret shown in Figure 1 was used. The casting solution was contacted with the polyester fiber braided tube in the spinneret (the height of the spinneret cavity was 10 cm) by the concentric circular composite spinning technique, the spinning was carried out at 140°C, the contact time of the casting solution with the braided tube was 2 seconds, and the contact pressure was 0.05 MPa. The support was pulled from bottom to top through the spinneret, and then the support passed through the annular doctor blade. The thickness of the polybenzimidazole primary film was controlled to be 100 μm, resulting in a polybenzimidazole primary film attached to the support. The excess casting solution flowed out through the casting solution outlet, and a part of the casting solution permeated into the support. When the polybenzimidazole primary film reached a length of 200 cm, it was transferred into an oven.
[0215] (3) The solvent in the polybenzimidazole primary film was completely evaporated at 200°C in a direct oven, and the residual solvent was removed through water washing and ethanol washing steps to form the finished membrane, the hollow fiber membrane.
[0216] The selective layer of the produced hollow fiber membrane was thick. There was no porous transition layer, and the selective layer was directly attached to the support at the outer surface of the support. The membrane had a weak bond between the selective layer and the support due to the absence of a transition layer, so that the selective layer was easy to fall off and the life was shortened. When the internal pressure exceeded 0.04 MPa, the selective layer was damaged. When the external pressure operation was adopted, the life was only 2000-5000 hours after multiple pressure changes.
[0217] The breaking strength of the prepared hollow fiber membrane was 166 MPa. Under a test pressure of 0.5 MPa and at 100°C, the pure helium permeability was 12.8 GPU, the pure hydrogen permeability was 11.6 GPU, the nitrogen permeability and the methane permeability were 0.11 GPU and 0.10 GPU, respectively. The hydrogen / nitrogen selectivity and hydrogen / methane selectivity were 105 and 116, respectively.
[0218] FIG. 10 shows SEM images of the hollow fiber membrane prepared in Comparative Example 1, and from left to right and top to bottom, images of the overall cross section, the selective layer, an enlarged selective layer, the outer surface, the inner surface, and a cross section of the support are arranged, respectively.
[0219] <Comparative Example 2> (1) Polybenzimidazole A7 was mixed with methanesulfonic acid and stirred at 150°C and 1.0 MPa pressure for 24 hours to achieve uniform mixing to prepare a mixed feed liquid (casting solution), where the mass contents were: 10 wt% polybenzimidazole, and 90 wt% methanesulfonic acid.
[0220] The structural unit of polybenzimidazole A7 is shown below:
[0221] [ka]
[0222] Here, polybenzimidazole A7 has a molecular weight of 12.6 × 10 4 The copolymer had a number average molecular weight of 1.01 g / mol.
[0223] (2) The mixed feed liquid was pushed out by a gear pump. Here, the spinneret shown in Figure 1 was used. The casting solution was contacted with the nylon braided tube in the spinneret (the height of the spinneret cavity was 10 cm) by the concentric circular composite spinning technique, the spinning was carried out at 140 °C, the contact time of the casting solution with the braided tube was 2 seconds, and the contact pressure was 0.1 MPa. The thickness of the polybenzimidazole primary film was controlled to be 30 μm via an annular doctor blade. When the polybenzimidazole primary film reached a length of 200 cm, it entered into a pure water coagulation bath and was wound up at a winding speed of 5 cm / min.
[0224] (3) Then, in a pure water bath, the solvent in the primary film was transferred into water, and the residual solvent was removed through water washing and ethanol washing steps to form the finished membrane, the hollow fiber membrane.
[0225] The average thickness of the produced hollow fiber membrane was about 600 μm. The thickness of the selective layer was about 500 nm. The outer diameter of the support was 1400 μm. The membrane had a weak bond between the selective layer and the support, and as a result, the selective layer was prone to falling off and the lifespan was shortened. When the internal pressure exceeded 0.05 MPa, the selective layer was damaged.
[0226] In addition, the breaking strength of the prepared hollow fiber membrane was 166 MPa. Under a test pressure of 0.5 MPa and at 100°C, the pure helium permeability was 28.5 GPU, the pure hydrogen permeability was 27.6 GPU, the nitrogen permeability and the methane permeability were 0.33 GPU and 0.27 GPU, respectively. The hydrogen / nitrogen selectivity and hydrogen / methane selectivity were 83.7 and 102.2, respectively.
[0227] <Comparative Example 3> (1) Polybenzimidazole A7 was mixed with N-methylpyrrolidone (NMP) and stirred at 50° C. and normal pressure for 24 hours to achieve a uniform mixture to prepare a mixed feed liquid (casting solution), where the mass contents were: 10 wt % polybenzimidazole and 90 wt % NMP.
[0228] The structural unit of polybenzimidazole A7 is shown below:
[0229] [ka]
[0230] Here, polybenzimidazole A7 has a molecular weight of 12.6 × 10 4 The copolymer had a number average molecular weight of 1.01 g / mol.
[0231] (2) The mixed feed liquid was pushed out by a gear pump. Here, the spinneret shown in Figure 1 was used. The casting solution was contacted with the nylon braided tube in the spinneret (the height of the spinneret cavity was 10 cm) by the concentric circular composite spinning technique, the spinning was carried out at 60 °C, the contact time of the casting solution with the braided tube was 2 seconds, and the contact pressure was 0.05 MPa. The thickness of the polybenzimidazole primary film was controlled to be 30 μm via an annular doctor blade. When the polybenzimidazole primary film reached a length of 200 cm, it entered into a pure water coagulation bath and was wound up at a winding speed of 5 cm / min.
[0232] (3) Then in a pure water bath, the solvent in the primary film was transferred into water to form a finished membrane, and the residual solvent was removed via water washing and ethanol washing steps.
[0233] The thickness of the selective layer of the prepared hollow fiber membrane was about 200 nm, the membrane structure was not dense, and the selectivity was low. When the internal pressure exceeded 0.1 MPa, the selective layer was damaged.
[0234] In addition, the breaking strength of the prepared hollow fiber membrane was 165 MPa. Under a test pressure of 0.5 MPa and at 100°C, the pure helium permeability was 107 GPU, the pure hydrogen permeability was 89.5 GPU, the nitrogen permeability and the methane permeability were 12.9 GPU and 11.4 GPU, respectively. The hydrogen / nitrogen selectivity and hydrogen / methane selectivity were 6.94 and 7.85, respectively.
[0235] <Example of helium purification> The helium-rich gas that is the feed gas contains a helium volume fraction of 20 volume %, a methane volume fraction of 17 volume %, a nitrogen volume fraction of 60 volume %, a hydrogen volume fraction of 1 volume %, a carbon dioxide volume fraction of 0.5 volume %, and an oxygen volume fraction of 1.5 volume %.
[0236] As shown in Figure 11, the helium-rich gas was produced: (1) Feed gas 1# first entered the cryogenic unit, where the temperature was -180°C and the pressure was 4MPa; (2) The indirect gas 2# obtained in step (1) entered into the catalytic dehydrogenation unit, where a small amount of pure oxygen was introduced as the combustion support gas during the combustion step to ensure that the catalytic reaction proceeded smoothly. Here, the catalyst was platinum and the temperature was 98°C; (3) The gas after combustion was dried (3#) and fed into a membrane unit, and then introduced into the membrane element prepared by the hollow fiber membrane of Example 4 of the present application to carry out the first and second stages of membrane separation operations, where the positive pressure side operating pressures of the membrane separation were 3 MPa and 3 MPa, respectively; (4) The helium-lean gas on the reprecipitation side was sent back to the cryogenic unit, and the crude helium product 4# on the permeate side was sent to the adsorption impurity removal unit for pressure swing adsorption operation, where the adsorbent was a combination of 5A molecular sieve, coconut shell activated carbon, and activated alumina, and the adsorption pressure was 10 MPa, resulting in the production of pure helium 5#.
[0237] Table 1 shows the gas composition at each stage of the helium purification process.
[0238] [Table 1]
[0239] Based on the above table, in the present invention, The helium concentration can be significantly increased by the low-temperature process; Hydrogen, which is difficult to separate from helium in the mixed gas, was effectively removed by the catalytic oxidation section. The gas was further intensively purified through membrane separation to obtain crude helium gas having a concentration of 99.75%; and the crude helium gas was further processed by pressure swing adsorption so that the helium concentration of the obtained product could reach 99.995% and meet the 4N grade specification; can be clearly understood.
[0240] Although the preferred embodiments of the present invention have been described in detail above, the present invention is not limited thereto. Within the scope of the technical concept of the present invention, many simple modifications can be made to the technical solutions of the present invention, including the combination of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the disclosure of the present invention, and all of them are encompassed by the protection scope of the present invention. [Brief description of the drawings]
[0241] [Figure 1] FIG. 2 is a schematic diagram of a spinneret configuration used in the production of the primary film and transition layer of the present invention. [Diagram 2] FIG. 2 is a schematic diagram of a process of the present invention for producing a primary film and a transition layer using the spinneret of FIG. 1. [Diagram 3] 1 is a schematic cross-sectional SEM image of a hollow fiber membrane prepared in Example 1 of the present invention. [Figure 4] 1 is a cross-sectional SEM image of the selective layer of the hollow fiber membrane prepared in Example 1 of the present invention. [Diagram 5] 1 is a cross-sectional SEM image of the inner surface of a hollow fiber membrane prepared in Example 1 of the present invention. [Figure 6] 1 is a SEM image of the outer surface of the hollow fiber membrane prepared in Example 1 of the present invention. [Figure 7] 1 is a SEM image of the inner surface of the hollow fiber membrane prepared in Example 1 of the present invention. [Figure 8] 1 is an SEM image of the hollow fiber membrane prepared in Example 4 of the present invention. [Figure 9] 1 is an SEM image of the hollow fiber membrane prepared in Example 5 of the present invention. [Figure 10] 1 is an SEM image of the hollow fiber membrane prepared in Comparative Example 1. [Figure 11] FIG. 1 is a schematic diagram of the present invention's method for purifying helium from a helium-rich gas.
Claims
1. A support; A selection layer; a transition layer between the support and the selective layer, the transition layer being at least partially embedded in the support.
2. the transition layer and the selective layer comprise the same polymer; Preferably, the transition layer and the selective layer comprise the same polymer, and the transition layer and the selective layer are formed from the same casting solution; More preferably, the transition layer and the selective layer comprise the same polymer, the transition layer and the selective layer are formed from the same casting solution, and the transition layer and the selective layer are formed by non-solvent induced phase separation and thermally induced phase separation, respectively.
3. both the transition layer and the selective layer comprise polybenzimidazole; Preferably, the polybenzimidazole is 5×10 4 ~30 x 10 4 and having a number average molecular weight of More preferably, the polybenzimidazole has a molecular weight of 5.6×10 4 ~28.7 x 10 4 The hollow fiber membrane according to claim 1 or 2, having a number average molecular weight of
4. The polybenzimidazole contains one or more structural units represented by formulas (A1) to (A8), 【Chemistry 1】 The hollow fiber membrane according to claim 3, wherein the polybenzimidazole preferably contains one or more structural units represented by formulas (A5) to (A8).
5. The support is a fiber braided tube or a hollow fiber membrane, preferably a microporous hollow fiber membrane, more preferably, the support is one or more selected from the group consisting of a fiber braided tube, a microporous polypropylene hollow fiber membrane, a microporous polyethylene hollow fiber membrane, and a microporous inorganic hollow fiber membrane; and / or The transition layer has a porous structure; and / or The hollow fiber membrane according to any one of claims 1 to 4, wherein the transition layer is obtained by non-solvent induced phase separation of a casting solution, preferably the transition layer is obtained by non-solvent induced phase separation of a polybenzimidazole-containing acid solution.
6. The average thickness of the hollow fiber membrane is 100 to 2000 μm, and / or the average thickness of the tube wall of the support is 50 to 2000 μm; and / or the average thickness of the selective layer is between 100 and 50,000 nm; and / or the average thickness of the transition layer is between 20 and 2000 μm; and / or the breaking strength of the film is 10 to 500 MPa; and / or at 100° C. and a test pressure of 0.5 MPa, the hydrogen / nitrogen selectivity is 110-300 and the hydrogen / methane selectivity is 125-360; and / or at 100° C. and a test pressure of 0.5 MPa, the helium / nitrogen selectivity is 140-390 and the helium / methane selectivity is 170-500; and / or at 25° C. and a test pressure of 0.5 MPa, the hydrogen / nitrogen selectivity is 200 to 550 and the hydrogen / methane selectivity is 200 to 860; And / or the membrane according to any one of claims 1 to 5, which has a helium / nitrogen selectivity of 240 to 900 and a helium / methane selectivity of 200 to 2000 at 25°C and a test pressure of 0.5 MPa.
7. 1. A method for producing a hollow fiber membrane, comprising: (1) preparing a casting solution containing a polymer; (2) applying the casting solution onto a support, where a portion of the casting solution penetrates into the support, thereby obtaining a primary film applied onto the support; (3) heating the primary film to form a selective layer; (4) injecting a bore fluid into the support to induce non-solvent induced phase separation of the casting solution that has penetrated into the support to produce a transition layer; and (5) optionally, after formation of the transition layer, heating to remove substantially all of the solvent; The method according to claim 1, further comprising:
8. The casting solution is applied onto the support using a doctor blade, preferably an annular doctor blade; and / or The support is pulled through the casting solution, preferably the support is pulled from the bottom up through the casting solution; and / or The method according to claim 7, wherein the support is a fiber braided tube or a hollow fiber membrane, preferably a microporous hollow fiber membrane, more preferably the support is one or more selected from the group consisting of a fiber braided tube, a microporous polypropylene hollow membrane, a microporous polyethylene hollow membrane, and a microporous inorganic hollow membrane.
9. 9. The method according to claim 7 or 8, wherein the casting solution is obtained by mixing the polymer, an acid, optionally a volatile solvent, and optionally additives, preferably the mixing conditions include a temperature of 25-160° C. and a duration of 2-72 hours.
10. the polymer is polybenzimidazole; Preferably, the polybenzimidazole is 5×10 4 ~30 x 10 4 and having a number average molecular weight of More preferably, the polybenzimidazole has a molecular weight of 5.6×10 4 ~28.7 x 10 4 The method according to any one of claims 7 to 9, wherein the copolymer has a number average molecular weight of
11. The polybenzimidazole contains one or more structural units represented by formulas (A1) to (A8), 【Chemistry 2】 The method according to claim 10, wherein the polybenzimidazole comprises one or more structural units represented by formulae (A5) to (A8).
12. The acid is a monoacid, preferably the acid is selected from the group consisting of hydrochloric acid, hydrofluoric acid, methanesulfonic acid, or mixtures thereof; and / or said volatile solvent is selected from the group consisting of methanol, ethanol, tetrahydrofuran, or mixtures thereof; and / or said additive is selected from the group consisting of lithium nitrate, calcium chloride, sodium chloride, potassium chloride, polyethylene glycol, polyethylene oxide, or mixtures thereof; and / or the bore fluid is selected from the group consisting of water, ethanol, methanol, isopropanol, acetone, tetrahydrofuran, or mixtures thereof; and / or the method of claim 10, wherein the amount of polybenzimidazole is 4-18 wt.%, the amount of the acid is 77-90 wt.%, the amount of the volatile solvent is 0-10 wt.%, and the amount of the additive is 0-5 wt.%, based on the total weight of the casting solution.
13. The coating conditions include a temperature of 20 to 240° C. and / or the heating conditions in step (3) include a temperature of 100 to 280° C.; And / or the contact time of the casting solution with the support is from 1 to 15 seconds.
14. The coating in step (2) is carried out by using a spinneret; the spinneret includes a support positioner, an annular doctor blade, and a core tube; the support positioner defines a cavity around the support; the cavity is for storing the casting solution; a casting solution inlet and a casting solution outlet are disposed on the cavity; one end of the cavity is connected to the support positioner to form a closed end; the other end of the cavity includes the annular doctor blade; the diameter of the annular doctor blade is greater than the width of the support positioner; and The method according to any one of claims 7 to 13, wherein the core tube is located within the inner tube of the support.
15. The method according to claim 7, wherein the hollow fiber membrane is the hollow fiber membrane according to claim 1.
16. A hollow fiber membrane produced by the method according to any one of claims 7 to 14.
17. 17. Use of the hollow fiber membrane according to any one of claims 1 to 6 and 16 for the separation of helium / nitrogen, helium / methane, hydrogen / nitrogen or hydrogen / methane.
18. 1. A method for purifying helium from a helium-containing gas, comprising: The method is characterized in that it comprises a step of carrying out membrane separation using the hollow fiber membrane according to any one of claims 1 to 6 and 16.
19. 20. The method of claim 18, comprising subjecting the helium-containing gas to condensation through a cryogenic process, catalytic dehydrogenation, membrane separation, and pressure swing adsorption impurity removal processes to result in purified helium.
20. The conditions of the condensation treatment include a temperature of −220° C. or higher; Preferably, the condensation treatment conditions include a temperature of −210° C. to −150° C. and a pressure of 0.2 MPa to 10 MPa; More preferably, the conditions of the condensation treatment include a temperature of −180° C. to −150° C. and a pressure of 3 to 10 MPa; and / or The catalytic dehydrogenation conditions include a temperature of 60 to 120° C., preferably 60 to 110° C.; and / or The catalytic dehydrogenation is carried out in the presence of oxygen and a catalyst; the catalyst is a noble metal catalyst; Preferably, the catalyst is selected from the group consisting of Pt, Pb, Rh, Ru, or Au; More preferably, the catalyst is selected from the group consisting of Pt, Pb, or Au; and / or The conditions of the membrane separation treatment include that the pressure on the positive pressure side of the membrane separation is higher than the pressure on the permeate side of the membrane separation, preferably, the pressure on the positive pressure side of the membrane separation is 0.2 to 10 MPa, and more preferably, the pressure on the positive pressure side of the membrane separation is 0.5 to 10 MPa; and / or The conditions of the pressure swing adsorption impurity removal treatment include an adsorption pressure of 0.2 to 15 MPa, preferably 10 to 15 MPa; and / or 20. The method of claim 19, wherein the adsorbent used in the pressure swing adsorption impurity removal process is selected from one or more of the group consisting of activated carbon, molecular sieves, metal-organic framework (MOF) materials, and activated alumina.
Citation Information
Patent Citations
Polybenzimidazole hollow fiber membranes and method for making an asymmetric hollow fiber membrane
US20160375410A1